Laboratory Study: Comparison of Physical Properties of XCD Polymer Drilling Mud and PHPA - Fattahanisa, Aqlyna; Yanti, Widia; Rizkina Rangga Wastu, Apriandi; Ristawati, Arinda; Setiati, Rini; Fadliah; Poluan, Chris Elvano; Juanda, Firdaus (Penerbitan Universitas Trisakti, 2023)
The physical properties of the drilling mud greatly affect the success of the mud in lifting cuttings. The value of the physical properties of the drilling mud that is not in accordance with the required specifications can make cutting removal not optimal. In this study, an analysis of the physical properties of XCD Polymer and PHPA drilling mud will be carried out at temperatures of 100 oF, 200 oF, and 300 oF. This research is experimental which will test the characteristics or physical properties of the mud used. At the beginning of testing the physical properties of the XCD Polymer and PHPA mud using the initial composition of each of these muds, the results obtained did not fit into the mud specifications that had been determined due to the influence of the temperature increase. If you continue to use the same mud composition, the higher the temperature, some of the physical properties of the drilling mud will decrease. To overcome this problem, additives are added to the mud composition at each temperature to be tested. This is done so that the results of testing the value of the physical properties of the mud tested at each temperature are in accordance with predetermined specifications. After re-testing using the composition of the mud that has been added with additives, the results obtained from the two tested muds are the density value of 8.9-11.2 ppg, viscosity of 24-33 sec/qt, plastic viscosity of 20-33 cps, yield point of 21-28 lb/100 sqft, gel strength 10 seconds and 10 minutes respectively of 4-6 lb/100 sq. ft and 6-8 lb/100 sqft, filtration loss of 1.9- 4.6 ml, the thickness of the mud cake is 0.6-1 ml, and the pH is 9-10.